Electrochemical and Post-Mortem Degradation Analysis of Parallel-Connected Lithium-Ion Cells with Non-Uniform Temperature Distribution. Issue 10 (8th October 2021) - Gonzalez Malabet, Hernando J.; Cavalheiro, Gabriel M.; Iriyama, Takuto; Gabhart, Austin; Nelson, George J.; Zhang, Guangsheng
Abstract : Prior work on Li-ion cells which were parallel-connected in a stack and subjected to long term cycling showed that non-uniform temperature distribution caused non-uniform and accelerated degradation. To elucidate the degradation mechanisms, electrochemical and post-mortem degradation analysis were performed. Electrochemical impedance spectroscopy analysis suggested that the main degradation mechanism for the middle cell was a solid electrolyte interface (SEI) layer growth. Nevertheless, post-mortem analysis using X-ray diffraction, optical microscope, and scanning electron microscopy paired with energy dispersive X-ray spectroscopy shows the presence of Li2 CO3 in both baseline and middle cell anodes. This points towards a combined degradation mechanism of SEI layer growth and lithium plating. A combination of microstructural particle cracking and lithium plating is considered the main mechanism for blocking the anode's porosity network, which hindered further lithium diffusion, resulting in the abrupt failure for the middle cell. The observation and quantitative analysis provides insight into the performance and reliability impacts of non-uniform conditions within lithium-ion batteries.